Co-delivery of Cisplatin(IV) and Capecitabine as an Effective and Non-toxic Cancer Treatment - Xiao, Xiao; Wang, Ting; Li, Leijiao; Zhu, Zhongli; Zhang, Weina; Cui, Guihua; Li, Wenliang (Frontiers in Pharmacology, 2019)
A strategy for preparing composite micelles containing both cisplatin(IV) (CisPt(IV)) prodrug and capecitabine using a co-assembly method is described in this study. The composite micelles are capable of an effective release of the anticancer drug cisplatin(II) (CisPt(II)) and capecitabine via acid hydrolysis once they are internalized by cancer cells. Moreover, the composite micelles display a synergistic effect in vitro and the combination therapy in the micellar dosage form leads to reduced systemic toxicity and enhanced antitumor efficacy in vivo.